Use of Carbon Nanotubes To Enhance The Physical and Mechanical Properties of Wood Composites - Muhammad Haziq, Sahimi (2012)
Medium Density Fiberboard had been widely used in the furniture construction. Malaysia is one of the develop country which is produce MDF board but less competitive due to lack of mechanical properties. This research is about to increase the productivity of Medium Density Fiberboard (MDF) by mixing the Carbon Nanotubes (CNT) as filler. The Carbon Nanotubes would increase the thermal and mechanical properties of MDF. The main purpose of this research is to enhance the mechanical properties of the wood composite boards and the surface smoothness of the boards. Some of the problems for using Carbon Nanotubes are the uniform dispersion in Urea Formaldehyde. To solve that problem, the Carbon Nanotubes have to undergo treatment with acid solution. The treated CNTs can be used in the manufacturing of MDF boards. The different amount of CNTs will be used for comparing the results. The result shows that, the increasing amount of CNTs had improved the MOR, IB and Thickness Swelling values. The 5.0% of CNTs show the greatest value of MOR, IB and Thickness Swelling. So it proved that the CNTs can improve the mechanical properties of wood composites. As a conclusion, the improvement of mechanical properties of wood composites will affect the production of wood composites in Malaysia. Moreover, it should increase the demand of wood composites and the uses of wood composites around Malaysia and can be exported outside Malaysia.